Dense molecular gas in the nearby low-metallicity dwarf starburst galaxy IC 10 - Kepley, Amanda A.; Bittle, Lauren; Leroy, Adam K.; Jiménez-Donaire, María J.; Schruba, Andreas; Bigiel, Frank; Gallagher, Molly; Johnson, Kelsey; Usero, Antonio (The astrophysical journal, 2018)
Dense molecular gas and star formation are correlated in galaxies. The effect of low metallicity on this relationship is crucial for interpreting observations of high-redshift galaxies, which have lower metallicities than galaxies today. However, it remains relatively unexplored because dense molecular gas tracers like HCN and HCO+ are faint in low-metallicity systems. We present Green Bank Telescope observations of HCN(1-0) and HCO+(1-0) on giant molecular cloud (34 pc) scales in the nearby low-metallicity () starburst IC 10 and compare them to those in other galaxies. We detect HCN and HCO+ in one and three of five pointings, respectively. The values are within the range seen in other galaxies, but are most similar to those seen in other low-metallicity sources and in starbursts. The detections follow the fiducial - and - relationships. These trends suggest that HCN and HCO+ can be used to trace dense molecular gas at metallicities of 1/4 Z ⊙, to first order. The dense gas fraction is similar to that in spiral galaxies, but lower than that in U/LIRGs. The dense molecular gas star formation efficiency, however, is on the upper end of those in normal galaxies and consistent with those in U/LIRGs. These results suggest that the CO and HCN/HCO+ emission occupy the same relative volumes as they do at higher metallicity, but that the entire emitting structure is reduced in size. Dense gas mass estimates for high-redshift galaxies may need to be corrected for this effect.